Exercise duration as apredictor ofcardiovascular disease in arterial hypertension. Data from a 6-year follow-up study. (25th November 2020) - Leontsinis, I; Kasiakogias, A; Mantzouranis, M; Fragoulis, F; Andrikou, I; Tzorovili, E; Tatakis, F; Karaminas, N; Kouremeti, M; Manta, E; Zammanis, I; Antoniou, C; et al.
Abstract: Background: Current hypertension guidelines necessitate an individualized cardiovascular risk assessment through a process that includes several parameters and remains challenging. Exercise capacity has been strongly associated with prognosis in cardiovascular disease and can be easily assessed by the exercise treadmill test (ETT). Purpose: The aim of the present study was to investigate theprognostic role of exercise capacity for future cardiovascular events in a cohort of essential hypertensive subjects. Methods: We followed up 1037 hypertensive adults (mean age 56 years, 53% males) with no previous history of cardiovascular disease, for a mean period of 6±3 years. During the baseline visit all subjects underwent a complete echocardiographic study, office blood pressure measurements, ECG, routine blood testing and an ETT with a Bruce protocol.During follow-up, all subjects were reviewed at least annually. Exercise capacity was expressedwithexercise duration the distribution of which was split by the median (9min). Accordingly, the subjects were classified into those with high (51%) and low exercise capacity (49%). The cardiovascular endpoint of interest was the composite of coronary artery disease and stroke. Results: The incidence of cardiovascular eventsduring the follow-up period was 4.1% (35 cases of coronary artery disease and 10 cases of stroke).Cox regression analysis revealed that high exercise capacity was associated with a lower risk for future cardiovascular events (HR = 0.35 (95% CI 0.172–0.741, p=0.006). In multivariate models adjusting for standard clinical and laboratory cardiovascular risk factors this association was sustained. Conclusion: Exercise duration shows a significant prognostic value for future CV events among hypertensivepatients. Exercise capacity assessment by means of TTE could enhance the identification of asymptomatic hypertensives at higher risk. Funding Acknowledgement: Type of funding source: None